A teoria da intencionalidade nas obras de Husserl e de Gurwitsch: entre fenomenologia transcendental e psicologia da Gestalt - Santos, Hernani Pereira [UNESP] (2015)
Our goal is to analyze Edmund Husserl's theory of intentionality, as found in his 1913 text, Ideas Pertaining to a Pure Phenomenology and to a Phenomenological Philosophy, and, in parallel, Aron Gurwitsch's theory of intentionality, as formulated in his doctoral thesis, from 1929, entitled Phenomenology of Thematics and of the Pure Ego. We emphasize, on the one hand, the method used by the authors in order to establish their theories, and, on the other hand, the specific contents of each theory. The research aims to contribute to the elucidation of the role of Husserl and Gurwitsch in the history of psychology and philosophy, to the clarification of the possible relations between transcendental phenomenology and empirical psychology, and to provide a better understanding of phenomenological psychology, which can be developed from the theory of intentionality and from constitutive phenomenology. The dissertation begins with providing a historical and logical background for the problems related to the concepts of intentionality and psychological description, taking as depart the work of Franz Brentano. The first chapter introduces Husserl's theory of phenomenological reduction and his Cartesian motivation. The second chapter consists of a series of analyzes and descriptions of pure and transcendental consciousness. The third chapter consists of a presentation of the constancy hypothesis, of its rejection by Gestalt psychology and, then, of the analogy made by Gurwitsch between this rejection and phenomenological reduction. The fourth chapter consists of a presentation of the structural aspects of Gurwitsch's theory of intentionality. The fifth chapter deals with Gurwitsch's theory of attention. Finally, the sixth chapter presents the main problems which Gurwitsch sees in the egological conception of consciousness and the main contributions of his...